Venezia Analoga: Comprendere la città attraverso i progetti di Le Corbusier, Louis Kahn e Frank Lloyd Wright (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
Places and images are the references of our memory, which is also our knowledge and our identity. The analogous city: The work of the thesis was therefore to conceive an imaginary Venice implanted on the real one. Following Canaletto’s example, we have reinserted, not incidentally (since the projects, which we virtually rebuilt in Venice, literally needed to be built in those places), the projects of three of the greatest architects in the history of contemporary architecture. These are the Student House, “The Masieri Memorial”; on the Grand Canal by Frank Lloyd Wright (1953), the Hospital of Le Corbusier in San Giobbe (1965) and the Palazzo dei Congressi at the Arsenale by Louis Kahn (1968-1974). We tried to reconstruct the latest version of the respective projects, the one that came closest to the concrete eventual realization. This reconstruction was not intended to be the faithful virtualization of any projects built, since this would have been a utopian undertaking, but it wants to be a personal interpretation as consistent as possible with the material available. This procedure allowed us to analyze the way in which these architects were able to confront formally and philosophically with such an influential context, Venice, to reflect on how these projects could have changed the face of a city. The virtual reconstruction of these projects is not an advanced perspective vision, but the desire to insert this dynamic language to bring new contributions to architectural research.